Different nitrogen sources on the absorption and distribution of phosphorus in corn - Fernandes, Manlio Sylvestre; Arrélaga, Luis Enrique; Santos, Gabriel de Araújo (Pesquisa Agropecuaria Brasileira, 2014)
Dry weight and N and P uptake by corn (Zea mays L. var. Centralmex) were compared in greenhouse for soils treated with increasing P-levels (0, 10, 20, 40 and 60 ppm) and a fixed N-level (80 ppm) applied either as NO3 - or as NH4+ plus a nitrification inhibitor. No difference was found in dry matter content between NO3+ and NH4+ treatments but a positive effect was observed with increasing P-levels. Free-N (amino-N + NO3- - N) accummulated in the shoots of plants treated with low levels of P. Amino-N was the free-N main fraction in plants treated with NH4+ whereas NO3- - N was the free-N main fraction in plants treated with NO3-. Nitrogen accummulated more in shoots (66.8%) than in roots (33,18%) while P accummulated more in roots (61.4%) than in shoots (38.6%). At the highest P-levels in soil (40 and 60 ppm) the root/shoot ratio was higher for plants under NH4+ - N than under NO3- - N. Phosphorus and N contents expressed as percentage of dry weight were not good indicators of nutrient status for these nutrients. Free N pool, on the other hand, was very sensitive to low P levels in soil.
Keywords: nitrification inhibitor; free-N concentration; p-partition; P-stress levels